2001
DOI: 10.1021/ja0109343
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Catalyzed Cycloisomerization Reactions of Enynes

Abstract: PtCl(2) constitutes an efficient and practical catalyst for a set of different atom economical rearrangement reactions of enynes. This includes (i) a formal enyne metathesis reaction delivering 1,3-dienes, (ii) the formation of polycyclic vinylcyclopropane derivatives, and (iii) an unprecedented O-->C allyl shift reaction if unsaturated ethers are employed. Although these transformations produce significantly different structural motifs, they share a common mechanism comprising a cationic manifold triggered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
170
3
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(187 citation statements)
references
References 28 publications
6
170
3
8
Order By: Relevance
“…[8,9] The results are summarized in Scheme 7. In addition to the formation of 10-membered dienes 25, 26, 28, 31 and 32, the cycloisomerization was suitable for production of bicyclic products containing 12-membered dienes and 14-membered tetraenes (27 and 29).…”
Section: Scheme 2 a C H T U N G T R E N N U N G (Pphmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] The results are summarized in Scheme 7. In addition to the formation of 10-membered dienes 25, 26, 28, 31 and 32, the cycloisomerization was suitable for production of bicyclic products containing 12-membered dienes and 14-membered tetraenes (27 and 29).…”
Section: Scheme 2 a C H T U N G T R E N N U N G (Pphmentioning
confidence: 99%
“…They found that treatment of these substrates with a catalytic amount of PtCl 2 at elevated temperature (60-80 8C in toluene) resulted in the assembly of the corresponding azabicyclo-[4.1.0]heptenes (Scheme 16). [8,9] Mono-, di-, and trisubstituted alkenes efficiently participated in this process.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [410]hepmentioning
confidence: 99%
“…On the basis of these data, we propose the process detailed in Scheme 1 as the most likely mechanism for this transformation. Coordination of cationic gold(I) to the alkyne followed by nucleophilic addition of the pendant olefin produces cyclopropylcarbinyl 13 cation 27, which may have some gold(I) carbene character (28). The bicyclo[3.1.0]hexene product is generated by a 1,2-hydrogen shift onto a cation or a gold(I) carbene.…”
mentioning
confidence: 99%
“…The stereochemical course of the reaction may lead to the formation of three diastereoisomers; the relative orientation of the substituents on the spiro-fused lactones may be defined as symmetrical-syn, unsymmetrical and symmetrical-anti. [17] The X-ray structure confirms the stereochemistry as the symmetrical-syn diastereoisomer, which occupies an unusual higher Table 2. Further isomerisation of 2a and 2b by monocationic Pd(II).…”
Section: Anion Effectsmentioning
confidence: 64%